2005
DOI: 10.1186/1743-0003-2-31
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of clinical assessment of left unilateral spatial neglect using a head mounted display system (HMD) in rehabilitation engineering technology

Abstract: Unilateral spatial neglecthead mounted display systemvirtual realityclinical assessment Abstract Purpose: Unilateral spatial neglect (USN) is a common syndrome in which a patient fails to report or respond to stimulation from the side of space opposite a brain lesion, where these symptoms are not due to primary sensory or motor deficits. The purpose of this study was to analyze an evaluation process system of USN in various visual fields using HMD in order to understand more accurately any faults of USN operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The finding that RH patients missed significantly more left targets than the controls in the large-screen tasks but not in the Bells Test was in line with various previous studies comparing new computerized visuospatial and traditional tests (Deouell et al, 2005;Kim et al, 2010;Tanaka et al, 2005;Ulm et al, 2013;van Kessel et al, 2010). Hence, an absence of symptoms in simpler test environments is not necessarily consistent with observations in more complex ones (Blini et al, 2016;Bonato, 2015;Bonato et al, 2010Bonato et al, , 2012Hasegawa et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The finding that RH patients missed significantly more left targets than the controls in the large-screen tasks but not in the Bells Test was in line with various previous studies comparing new computerized visuospatial and traditional tests (Deouell et al, 2005;Kim et al, 2010;Tanaka et al, 2005;Ulm et al, 2013;van Kessel et al, 2010). Hence, an absence of symptoms in simpler test environments is not necessarily consistent with observations in more complex ones (Blini et al, 2016;Bonato, 2015;Bonato et al, 2010Bonato et al, , 2012Hasegawa et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…Variations in task complexity hinder the use of compensatory strategies, and reaction time measurements enhance precision (Bonato & Deouell, 2013). Traditional tests do not reach similar sensitivity (Deouell et al, 2005;Kim et al, 2010;Tanaka, Sugihara, Nara, Ino, & Ifukube, 2005;Tsirlin, Dupierrix, Chokron, Coquillart, & Ohlmann, 2009;Ulm et al, 2013;van Kessel et al, 2010van Kessel et al, , 2013 even if factors increasing discernment are introduced (Bonato et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found a higher sensitivity for the VR-based assessment method for polar target arrays compared to linear arrays and paper-pencil tasks. Besides these examples, other studies also showed a higher sensitivity of computerized neglect assessment (Tanaka et al, 2005;Broeren et al, 2007;Aravind et al, 2015). Detailed information regarding these studies is summarized in the review by Ogourtsova et al (2017).…”
Section: Introductionmentioning
confidence: 96%
“…The aim of this study was to evaluate a new head mounted display (HMD) system that has been devised for quantitatively assessing the visual recognition of patients with cerebrovascular diseases 18 , 19 ) . USN symptoms not disclosed by the ordinary line cancellation test were found by the HMD system.…”
Section: Introductionmentioning
confidence: 99%